Comparative profitability analysis of cowpea and soybean enterprises in Niger State of Nigeria - Bwala, Madu Ali; Alani, Wasiu (Journal of the Bangladesh Agricultural University, 2020)
This study determined and compared the profitability of cowpea and soybean enterprises in Gurara area of Niger State, Nigeria. A multistage random sampling procedure was used to draw one hundred and twenty (120) samples for the study. Data used for the study were elicited through structured questionnaire. Descriptive statistics, farm budgeting techniques and the T-test were used for the analyses. Results show that cowpea and soybean farmers in the study area are operating at a small scale, where the mean farm sizes for cowpea and soybean farmers were found to be 1.82 and 2.85 hectares respectively. The profitability analysis revealed both cowpea and soybean enterprises to be profitable. However, cowpea production was discovered to be more profitable than that of soybean. The cowpea enterprise had a gross margin of $698.82 and a net farm income of $659.99 per hectare. The return on Dollar invested was found to be 1.43 (143%) for cowpea. The Gross Margin for soybean enterprise was estimated at $186.80 per ha, and a Net Farm Income of $153.59 per hectare was calculated. The return on Dollar invested for soybean was estimated at 0.38 (38%). The T-test analysis showed that the difference in the profitability of cowpea and soybean enterprises is significant at the 5% level of significance (t-tabulated value = 1.980, t-calculated =1.926). Both cowpea and soybean farmers experienced challenges in their farm operations. The challenges identified include poor credit facility, high cost of labour, lack of capital, and inadequate extension contact. Others include lack of market price information, and poor access to market centers due to bad roads. The study therefore recommends that credit facilities should be made available especially for cowpea farmers. Also, extension service coverage by concerned government agencies should be intensified. J Bangladesh Agril Univ 18(2): 471–478, 2020 https://doi.org/10.5455/JBAU.98958